Nurses' perceptions of caring for dying patients in an open critical care unit: a descriptive exploratory study - McCallum, Amanda; McConigley, Ruth (Mark Allen Publishing Ltd, 2013)
Background: Nurses in critical care areas play a vital part in providing end-of-life care and recognise that an ideal death should be peaceful, dignified, and comfortable. However, environmental restrictions in critical care units can make a peaceful death unachievable and can havea profoundly negative impact on end-of-life care.Purpose: To describe the provision of end-of-life care in an open high-dependency unit.Method: A descriptive exploratory approach was used involving semi-structured interviews with a purposive sample of five registered nurses working in the high-dependency area at a major teaching hospital. The interviews were audio taped and transcribed. Thematic analysis was used to code the data and identify themes.Results: Three themes emerged from the data. The core theme was ‘the nurse as protector’. The two other themes were ‘conflict of care’ and ‘peace and quiet’. Within these themes, characteristics of an ideal death were identified and barriers to providing an ideal death were acknowledged.Conclusion: This study illustrates nurses’ perceptions of caring for dying patients in an open critical care unit. This environment influences the development of the nursing role as protector and presents barriers to achieving an ideal death.